Integrated biocontrol strategies using indigenous fungal endophytes Aspergillus fumigatus and Curvularia lunata against wheat stripe rust - Khan, Salman; Rahman, Khalil Ur; Gul, Humaira; Rauf, Mamoona; Gechev, Tsanko; Arif, Muhammad; Ali, Akhtar; Ali, Sajid (Frontiers in Microbiology, 2025)
BackgroundWheat stripe rust, caused by Puccinia striiformis f. sp. tritici (Pst), is a major pathogenic threat, particularly in regions with favorable moist conditions during the growing season, resulting in significant commercial losses. This study investigates the variations in wheat plant responses to pathogen stress and the potential biocontrol effects of fungal endophytes against stripe rust. Due to the challenges associated with culturing the obligate biotrophic basidiomycete fungi on artificial media, there is a dire need for eco-friendly, economical, and safe biocontrol alternatives.MethodsWe explored the biocontrol potential of two indigenous fungal endophytes, Curvularia lunata (DT-4) and Aspergillus fumigatus (DT-8), against wheat stripe rust in two susceptible wheat varieties.ResultsOur results revealed that both fungal strains significantly improved wheat grain germination and secondary metabolites induction in two wheat varieties. The Morocco variety showed enhanced seed germination (63.6 % DT-4, 72.7% DT-8), plant growth (48.9% DT-4, 55.6% DT-8), and seedling fresh weight (126% DT-4, 110% DT-8), highlighting their potential as biocontrol agents. Treated wheat plants with DT-4 and DT-8 consortia after infection with strip rust (Puccinia striiformis) suspension (SR-S) exhibited enhanced resistance to stripe rust, evidenced by increased antioxidant enzyme activities SOD, CAT, and POD (54.5, 54.6, 112.7%), reduced lipid peroxidation (42.1%), and decreased disease severity (80%). Similarly, wheat grain of TD-1 variety treated with fungus culture filtrate showed maximum germination for seeds (38.5% DT-4, 53.8% DT-8), plant growth (54.5% DT-4, 31.8% DT-8), and seedling fresh weight (125% DT-4, DT-8). A significant increase is observed in the antioxidant enzyme activities SOD, CAT, and POD (59.2, 71.9, 104.6%), reduction in lipid peroxidation (32.8%), and decreased disease severity (80%).ConclusionThese findings suggest that Aspergillus fumigatus and Curvularia lunata induce the anti-pathogenic metabolites, defense-related protein, antioxidant enzymes, resistance genes, salicylic acid (SA), and jasmonic acid (JA) biosynthesis. Together, these responses enhance the overall defensive capacity of wheat against stripe rust, providing a sustainable and ecologically friendly alternative to synthetic fungicides for controlling wheat stripe rust.